Examining the Relationship Between Financial Leverage and Shareholder Payoffs: Insights from the Pharmaceutical Sector in India (Global Journal of Management and Business Research, 2024)
This paper empirically examined the effect of financial leverage on payoffs to shareholders, a study of listed Pharmaceutical firms in India. Using annual panel data for a period of 13 years, ranges from 2007-08 to 2019-20 with the application of econometric techniques. The empirical results show that Long Term Debt to Total Assets (LTD/TA) have positive relationship, while Total Debt to Total Assets (TD/TA) has negative relation with Return on Assets (ROE). Thereby evidenced that financial leverage has significant effect on firm performance specifically in terms of payoffs to shareholders particularly during Normal/Bullish phase of Economy when measured through EPS & ROE in sample Pharmaceutical Companies in India.
Keywords: financial leverage; earnings per share; return on equity